Patient-Specific Instrumentation in Total Knee Arthroplasty - Jauregui, Julio J.; Cherian, Jeffrey J.; Kapadia, Bhaveen H.; Banerjee, Samik; Issa, Kimona; Harwin, Steven F.; Mont, Michael A. (The Journal of Knee Surgery, 2014)
Patient-specific instrumentation (PSI) is a technology that allows the surgeon to perform a total knee arthroplasty (TKA) potentially more easily with preformed cutting blocks and jigs, which are developed from preoperative computed tomographic or magnetic resonance image scans of the knee. It was introduced with the goal of reducing surgical time, minimizing costs, improving alignment, and reducing radiographic outliers when performing a TKA. Although multiple reports have demonstrated that PSI can reduce the amount of trays and instrumentation required, operative time, and turnover rates, this has not been extrapolated to an overall cost reduction. This is potentially related to the costs of preoperative imaging and the intrinsic costs of production of the patient-specific guides. With the present technology, it is also controversial whether improvements in alignment can be achieved. In addition, it remains to be seen whether this will lead to a reduction in costs and improvements in clinical, radiographic, and functional outcomes. As PSI is relatively new, there is a paucity of long-term studies, which makes it difficult to predict whether long-term improvements in implant survivorship will lead to substantial improvements in patient function, overall outcomes, or cost benefits.
Keywords: patient-specific instrumentation; total knee arthroplasty; preoperative templating